Crafting, Collecting, and Clubbing in the Victorian Drawing Room - Arias-Doblas, María Rosario; Monrós Gaspar, Laura (My University, 2022)
In her volume Inside the Victorian Home (2003), Judith Flanders scrutinizes the space of home and domesticity as a microcosm of the ideal society of the nineteenth century. Considering Flanders’ ideas as a point of departure, the aim of this paper is to explore the sociocultural representation of domesticity as a rupture of the traditional perception of Victorian society from the point of view of the theory of separate spheres. To this purpose we consider the middle-class home as a crossroad between the public and the private, the Victorian drawing room as an interstitial space of negotiation between public and private, as well as the Victorian domestic environment as porous and fluid.
Keywords: Gran Bretaña -- Historia -- 1837-1901 (Victoria); Cultura material; Victorianism; Material culture; Victorian drawing room